Higher vs. Lower DP for Ventilated Patients with Acute Respiratory Distress Syndrome: A Systematic Review and Meta-Analysis. (18th July 2019) - Chen, Zhen; Wei, Xuxia; Liu, Genglong; Tai, Qiang; Zheng, Donghua; Xie, Wenfeng; Chen, Li; Wang, Ganping; Sun, Jia-Qi; Wang, Siqi; Liu, Na; Lv, Haijin; et al.
Abstract : Objectives . Driving pressure (DP) has recently become a promising mediator for the identification of the effects of mechanical ventilation on outcomes in acute respiratory distress syndrome (ARDS). The aim of this study was to systematically and quantitatively update and assess the association between DP and mortality among ventilated patients with ARDS. Methods . PubMed, the Cochrane Library, ISI Web of Knowledge, and Embase were systematically searched from inception to June 2018. Two investigators conducted the literature search study selection, data extraction, and quality evaluation independently. RevMan 5.3 software was used for all statistical analyses. Results . A total of seven studies comprising 8010 patients were included in this meta-analysis. Higher DP showed a significant association with higher mortality (pooled risk ratio, 1.10; 95% [CI], 1.05–1.16; I 2 =58%). Sensitivity analysis indicated that one study significantly affected the stability of pooled results. One of the subgroups investigated, ARDS severity, could account for the heterogeneity. An exploratory post hoc subgroup analysis and higher DP significantly increased mortality in the mild to severe ARDS subgroup (RR 1.28; 95% [CI], 1.14–1.43;  I 2 =0), but not in the moderate to severe ARDS subgroup (RR 1.18; 95% [CI], 0.95–1.46;   I 2 =52%). Conclusion . Higher DP was significantly associated with an increased risk of death among ventilated patients with ARDS. But it did not seem to predict prognosis to moderate to severe ARDS. Future prospective randomized clinical trials are needed to verify the results of this meta-analysis and address the unresolved questions about optimum cutoff values for DP. Trial Registration . This trial is registered with PROSPERO (CRD42018102146 ), on 11 August 2018.